Utility of Sacrifices: Reorientation of the Utility Theory - Arun GC (Review of Business and Economics Studies, 2023)
Utility theory is a pivotal concept in economics that provides insights into how an individual is motivated to act under budget constraints. The main assumption of this theory and the entire field of economics is that a rational human being and an individual derive utility from the consumption of goods and services under given budget constraints. The aim of this article is to explore these fundamental assumptions and introduce a new theoretical framework for deriving utility, which is termed the “utility of sacrifices”. Various methods were employed in the study, including a review of existing literature, an analysis of prevailing theories, and observations in real-world scenarios. The results show that, through observations, a "rational" human being derives utility from both consumption and voluntary sacrifices. Therefore, in conclusion, it is proposed that the total utility of an individual is the sum of these two components. This theoretical framework provides a more comprehensive understanding of human decision-making and behavior in economics. It also provides novel insights for future research and applications in economics.